Lunggaycrunch: evaluating online business potential for malunggay chips - CAMPOLLO, Kem Rose B. Cruzada, Jane Raven M. Igloria, lfrancis P. Matias, Sylvia R. 4 0 16; 5
u
Feasibility Study : (BSBA major in Human Resource and Operations Management) - Pamantasan ng lungsod ng Maynila
Keywords: 2 -- 0; 6; 20; 20; 2